The Orientation Of Multiple Intelligence Framework In Learning Arabic In Digital Era - Apri Wardana Ritonga (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2021)
Digital-based Arabic learning has become a necessity that must be done by every teacher in the technology era. The concept of multiple intelligences is present as an answer to some of the perceptions that reveal that there are students who are stupid in the field of language. This study intends to explore the theoretical framework of multiple intelligences in learning Arabic in the digital era. Using a qualitative approach with library research methods in describing research findings. Research data was obtained from primary and secondary sources in the form of articles, proceedings and books. The collected data is then presented using a descriptive content analysis technique deductively. This research shows that the digital era is a great opportunity for teachers in compiling multiple intelligences-based learning that is tailored to the conditions and needs of students. In addition to the above aspects, the concept of multiple intelligences adopted in Arabic learning provides room to compete with other subjects that have applied multiple intelligences first. To refine these findings, further research is needed to test the learning outcomes using multiple intelligences with conventional learning without the concept of multiple intelligences.